مرزا حامد بیگ۔۔۔فن اور شخصیت: ایک تنقیدی جائزہ (Contemporary Journal of Social Science Review, 2025)
Mirza Hamid Baig, a distinguished figure in Urdu literature, was born on August 29, 1947, in Karachi. His early life was marked by frequent relocations due to his father’s government service, exposing him to diverse cultural and social environments across Sindh and Punjab. From a young age, he developed a passion for storytelling, influenced by traditional oral narrations in his ancestral village, Kamala. His academic journey began in Sindhi-medium schools before transitioning to Urdu-medium education. He was profoundly inspired by cinema, art, and literature, which later shaped his literary career. The socio-cultural complexities of Sindh, including encounters with law enforcement, criminal activities, and historical events such as the capture of the infamous dacoit Shuja Bhambhro, left a lasting impact on his creative mind. This study critically examines his formative years, influences, and early experiences that contributed to his artistic and literary development.